TREN PENGGUNAAN ANTIBIOTIKA LINI 3 DI RS X BEKASI PERIODE TRIWULAN I TAHUN 2020 DIBANDINGKAN DENGAN TRIWULAN IV TAHUN 2019 - Hasanah, Kurniatul (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2022)
Antibiotics are the most widely used drugs in the treatment of infections caused by bacteria. Resistance of microorganisms to antibiotics, pharmacokinetic and pharmacodynamic factors, drug interactions and side effects and cost factors are needed to be considered in their use. The use of antibiotics needs to be evaluated quantitatively and qualitatively. The study was conducted to determine and evaluate the use of line 3 antibiotics quantitatively in the X Bekasi Hospital in the first quarter of 2020 compared to the fourth quarter of 2019. It was descriptive study with retrospective data collection using total sampling technique. There are 13 types of antibiotics that are included in the line 3 antibiotics used at X Bekasi Hospital. The percentage of use of line 3 antibiotics in the first quarter of 2020 compared to the fourth quarter of 2019 increased by 26.9% for the use of amikacin 250 mg injection but decreased by 100% for the use of amikacin 500 mg injection, increased by 17.8% for the use of meropenem 0.5 g injection but decreased by 16.1% for the use of meropenem 1 g injection, decreased by 100% for the use of imipenem-cilastatin injection, linezolid 600 mg injection and vancomycin 500 mg injection, decreased by 212.5%, 53.6%, 41.2% and 69.2% each for the use of doripenem 500 mg injection, decreased, ceftazidime 1 g injection, cefepime 1 g injection and piperacillin tazobactam injection, and increased 75% for the use of tigecycline 50 mg injection. The use of line 3 antibiotics in X Bekasi Hospital was very large and varied in the fourth quarter of 2019 compared to the first quarter of 2020. A very significant amount was seen in the use of imipenem-cilastatin injection, linezolid 600 mg injection and vancomycin 500 mg injection.